Analisis Pengaruh Sistem Informasi Akuntansi Penerimaan Kas dalam Peningkatan Pengendalian Intern (Studi pada PT. PD. Paya Pinang) - Agung Setiawan; Hendra Harmain (Journal of Accounting, Management, Economics, and Business (ANALYSIS), 2023)
PT. PD. Paja Pinang is a company that is engaged in the field of palm coconut and rubber planting which includes 3 companies of them: PT. P. Paya Pinang, P. D. Hasjrat Tjipta, PT. Source Sawit Makmur located in Medan, the company became the focus of this research. A good accounting information system involves internal control, which both run side by side. The research is aimed at finding out whether the company's cash receipt accounting information system runs in accordance with existing procedures, and can improve internal control. This research uses a qualitative approach, in which researchers use data collection techniques through observations, interviews, and libraries. (Library research). The results of the research show that PT. PD. Paya Pinang has implemented the cash receipt accounting information system has worked well in accordance with the procedures that have been made by the company and can improve internal control well.